Sustainable Fashion: Second-hand Fashion Trends and Its Impact on Local Fashion Brands in Indonesia - Meiko Fairuzia Ardiany; Mas Rahmah (Center for Risk Management & Sustainability and RSF Press, 2025)
This study analyzes the impact of the second-hand fashion trend on the sustainability of local fashion in Indonesia from environmental, economic, and regulatory perspectives. The research employs a qualitative approach using narrative analysis based on secondary data. The results indicate that although this trend increases awareness of sustainability and supports the development of circular economy, it also raises concerns regarding the local textile industry due to the widespread illegal import of used clothing. Regulations and existing laws have not been fully effective in curbing the influx of imported used clothing, which is influenced by low public awareness and limited supervision by legal authorities and relevant stakeholders. The study emphasizes the need for synergy among the government, industry, and society in managing the second-hand fashion trend to support economic and environmental sustainability in Indonesia.